STEAM-Based Learning with Loosepart Media Improves Critical Thinking and Creative Thinking Skills of Group B Children - Eri Meriah; Maria Goreti Rini Kristiantari; Didith Pramunditya Ambara (Universitas Pendidikan Ganesha, 2025)
Monotonous learning activities and a lack of development of critical thinking skills in students cause low critical and creative thinking skills. Based on this, the purpose of this study is to analyze the effect of STEAM Based Learning with Loose Part Media on the Critical Thinking and Creative Thinking Skills of Group B Children. The research method employed in this study is a quasi-experimental design. The design of this study employs a post-test-only control group design. The population in this study consisted of 5-to 6-year-old kindergarten students, with a sample size of 30 students. In this study, the sampling technique employed was purposive sampling, with a total sample of 30 students. The method used in collecting data was a test. The instrument used for data collection was a checklist sheet with a rating scale. The data analysis technique used the t-test. The results of the study showed a significant difference between the experimental group and the control group in terms of critical thinking skills. The average difference value (indicates that the average score of children's critical thinking skills in the experimental group given treatment is higher than that of the control group. Second, there is a significant difference between the experimental group and the control group in terms of creative thinking skills. The average difference value indicates that the average score of the children's creative thinking skills in the experimental group, given the treatment, is higher than that of the control group. It is concluded that the STEAM approach, assisted by Loose Parts media, has a positive effect on improving critical and creative thinking skills in children in Group B.